Gendered Parenting and Language Achievement: A Comparative Study of Children from Single-Mother and Single-Father Families in Arabic Language Learning - Sufian, Muhammad; Erlina; Sabrina Octariani (Women, Education, and Social Welfare, 2024)
This study investigates differences in Arabic language achievement between students raised by single mothers and single fathers and examines how affective support, academic control, and religious orientation influence students’ learning outcomes in Islamic education contexts. Employing a quantitative ex post facto design, 120 secondary students (60 from single-mother and 60 from single-father families) participated through a combination of Likert-scale questionnaires and standardized Arabic tests. Data were analyzed using t-tests, Pearson correlations, and multiple linear regression at a 0.05 significance level. The results reveal a significant difference between groups (p < 0.05), where children from single-mother families achieved higher mean scores (M = 84.60) than those from single-father families (M = 79.35). Regression analysis shows that affective support (β = 0.396), religious orientation (β = 0.327), and academic control (β = 0.181) jointly predict 52.3% of Arabic learning achievement (R² = 0.523). The findings highlight that emotional warmth and religious values are stronger determinants of success in Arabic language learning than academic supervision alone. Theoretically, the study extends Gendered Parenting Theory and Sociocultural Learning perspectives within Islamic education, while practically, it emphasizes the importance of family-based affective and spiritual engagement to foster student motivation and language mastery.